ANALYSIS OF STUDENT DIFFICULTIES IN SOLVING QUESTIONS UNDERSTANDING MATHEMATICS CONCEPTS IN GEOMETRY MATERIALS - Reva Sefti Repriani; Al Jupri (Program Studi PGSD Universitas Flores, 2025)
Although geometry is important in mathematics education, many students have difficulty understanding and applying its concepts, which can affect their academic performance. This study analyzes students' difficulties in solving problems related to understanding elementary school geometry concepts. Assessment of the concept understanding aspect aims to decide the extent of students' ability in understanding mathematical concepts with indicators of the causes of students making mistakes in solving problems based on the Newman procedure: a) reading errors; b) comprehension errors; c) transformation errors; d) process skills errors and; e) encoding errors. This study is a qualitative study with a case study to analyze elementary school students' understanding of mathematical concepts in solving problems about flat shapes. In deciding the subjects of this study, a purposive sampling technique was used by selecting and sorting subjects that met the predetermined criteria. The subjects of this study were all fifth-grade students at an elementary school in Bandung Regency, totaling 33 students. The instrument in this study was a test of understanding mathematical concepts about shapes. The results showed that students who experienced reading errors were 9.09%, comprehension errors were 30.03%, transformation errors were 51.51%, process skill errors were 39.39%, and encoding errors were 30.03%.